Lipid-based nanoparticles via nose-to-brain delivery: a mini review - Xinchen, Yang; Jing, Tan; Jiaoqiong, Guan (Frontiers in Cell and Developmental Biology, 2023)
Central nervous system (CNS) disorders significantly affect the lives and health of millions of people worldwide. Despite many therapeutic drugs are available that could potentially target central nervous system disorders, their clinical utility is severely constrained by their inability to cross the blood-brain barrier (BBB). Fortunately, nanotechnology has been advanced to offers a solution to allow drugs reaching the targeted brain regions safely, efficiently, and precisely through nasal drug delivery system (NDDS), bypassing the BBB completely. This strategy can promote the drug accumulated in the targeted brain region, improve drug bioavailability, and minimal side effects and mucociliary clearance effectively. In this review, we elaborate recent advances in the use of lipid-based nanoparticles, involving liposomes, nanoemulsions, nanostructured lipid carriers, and solid lipid nanoparticles. Besides, we particularly introduced the nasal cavity physiological structure, and further summarized the nose-to-brain drug delivery pathways, including olfactory, trigeminal, and blood circulation pathway. Moreover, the mechanism and route of NDDS by various types of nanoparticles are also highlighted.